AB0053 ACTIVIN A AND FOLLISTATIN AFFECT THE INTERACTION OF ENDOTHELIAL CELLS AND RHEUMATOID ARTHRITIS SYNOVIAL FIBROBLASTS. (June 2019) - Aykara, Iris; Diller, Magnus; Rehart, Stefan; Müller-Ladner, Ulf; Neumann, Elena
Abstract : Background: Activin A and its antagonist follistatin are part of an autoregulatory cycle, which is well known in the hypothalamic-pituitary-gonadal axis. Activins also have an important function in autoimmune diseases, such as rheumatoid arthritis (RA). Due to inflammation, activin A is released systemically, causing an induction of its antagonist follistatin. The negative feedback mechanism is well described for hepatocytes, but seems to be inactive in synovial fibroblasts from patients with rheumatoid arthritis (RASF). Neoangiogenesis, which is mediated partially by local fibroblasts, is increased due to inflammation and tissue hyperplasia in RA synovium. Despite the fact that RASF contribute to cartilage destruction in RA and RASF are able to interact with endothelial cells, less is known about the effect of activin and follistatin in this context. Objectives: The aim of this study was to examine the effect of activin A and follistatin on the interaction of RASF and endothelial cells. Methods: Endothelial cells (HUVEC) were commercially obtained and RASF were isolated from synovial tissue of patients with RA undergoing joint replacement surgery, RASF and HUVEC were stimulated in mono-, or coculture with activin A (15ng/ml), follistatin (500ng/ml) and/or IL-1β (1ng/ml). The concentrations of activin A, follistatin, VEGF and IL-6 were measured by ELISA. Results: IL-1β induced the release of activin A 8-fold in RASF alone (p < 0.01, n=5) as well as in direct coculture with HUVECs 4-fold (p < 0.05, n=5). The stimulation with follistatin together with IL-1β reduced the activin A concentration produced by HUVECs 9-fold (p < 0.01, n=5) as well as in cocultures (10- fold, p<0.01) in comparison to stimulation with IL-1β alone. This reduction could not be observed in RASF monoculture. In HUVECs, the IL-6 release was reduced by 37.6% after stimulation with activin A and IL-1β (n=5, p<0.05) in comparison to the stimulation with IL-1β alone. In RASF monoculture the release of IL-6 was induced by 61.0% after stimulating with activin A combined with IL-1β in comparison to the stimulation with IL-1β alone. In direct coculture neither the induction, nor the reduction of the IL-6 concentration could be detected when stimulated with activin A and IL-1β. The release of VEGF was induced in RASF with IL-1β (89%), activin A (55%), activin A combined with IL-1β (148%), follistatin and IL-1β (84%) compared to unstimulated control. In coculture with HUVECs, the induction was less distinct than in monoculture (IL-1β: 75%, activin A: 22%, activin A and IL-1β: 101%, follistatin and IL-1β: 67%, n=4). Conclusion: The autoregulatory cycle of activin A and follistatin is active in endothelial cells and inactive in RASF. Due to the interaction of endothelial cells and RASF, the proinflammatory response of the RASF is weakened. This was shown in direct coculture with no induction in coculture compared to stimulation with activin A and IL-1β in RASF monoculture. Interestingly, in direct coculture, the effects of HUVECs appear to dominate resulting in a significant reduction of the activin A concentration in the presence of follistatin and IL-1β in comparison to RASF monoculture. References: [1] de Jong FH, Grootenhuis AJ, Klaij IA, Van Beurden WM: Inhibin and related proteins: localization, regulation, and effects. Adv Exp Med Biol1990;274:271-293. [2] de Kretser DM, O'Hehir RE, Hardy CL, Hedger MP: The roles of activin A and its binding protein, follistatin, in inflammation and tissue repair. Mol Cell Endocrinol2012;359:101-106 Disclosure of Interests: Iris Aykara: None declared, Magnus Diller: None declared, Stefan Rehart: None declared, Ulf Müller-Ladner Grant/research support from: Projekt supported by an unrestricted educational grant from Celgene GmbH., Elena Neumann: None declared